Using Nasal Self-Esteem to Predict Revision in Cosmetic Rhinoplasty. (28th August 2020) - Okland, Tyler S; Patel, Priyesh; Liu, George S; Most, Sam P
Abstract: Background: It would be useful if existing tools or outcomes measures could predict which patients are at greater risk of revision surgery following rhinoplasty. Objectives: The authors sought to determine if a single question assessing nasal self-esteem could be utilized to predict which patients are at greatest risk of revision surgery following rhinoplasty. Methods: The authors conducted a retrospective chart review of 148 patients who underwent cosmetic rhinoplasty. Results of pre- and postoperative Standardized Cosmesis and Health Nasal Outcomes Survey questionnaires and rates of revision or patient-initiated revision discussions (RD) were collected. Patients were stratified based on answers to Standardized Cosmesis and Health Nasal Outcomes Survey question 5 (SQ5), "Decreased mood and self-esteem due to my nose." Results: Of the 148 patients included in the analysis, 72.9% were women, and the mean age was 30.9 (15-59, standard deviation = 10.3) years. Those patients who selected 4 or 5 on SQ5 had an overall revision rate of 16.7% and 18.8%, respectively, and a RD rate of 27.8% and 31.25%, respectively. Those patients who selected 0 through 3 on SQ5 had an overall revision rate of 0% and an overall RD rate of 10.4%. Only SQ5 was predictive of revision and RD on logistic regression analysis ( P = 0.0484 and P = 0.0257) after Bonferroni correction. Conclusions: SQ5 appears to offer a useful adjunct to guide surgical management of the cosmetic rhinoplasty patient. Those patients who reported worse nasal self-esteem and associated mood preoperatively were more likely to request and undergo revision. Level of Evidence: 4: